Echolalia as communication behavior - Boksa, Ewa; Kominek, Andrzej (Logopedia Silesiana, 2022)
Echolalia is a natural phenomenon in the development of child speech. After 30 months of age, echolalia becomes a pathological phenomenon, most often associated with deficits in the ability to initiate and sustain social interaction. Researchers argue about the role of echolalia in the acquisition of language and communication skills of people with autism spectrum disorder. They are trying to answer the question of whether echolalia is an inhibiting factor in language acquisition or whether it can also be one of the main predictors of further speech development. The distinguishing of echolalia and echolalic speech in the communication of people with autism, proposed by Jacek Błeszyński, makes it necessary to revise the existing definitions of echolalia and present this phenomenon from the perspective of communication theories, among others, in the context of the concept formulated by Dan Sperber and Deirdre Wilson.